Quantum circuit-based quadratic nonlinear equation set solving method and device - AN NINGBO; DOU MENGHAN; LI YE (2023)
The invention discloses a quadratic nonlinear equation set solving method and device based on a quantum circuit, and the method comprises the steps: obtaining a target linear equation set, carrying out the conversion determination of the target linear equation set according to an initial quadratic nonlinear equation set, constructing a quantum circuit corresponding to a quantum linear solver, operating the quantum circuit, and carrying out the measurement. According to the method, a target linear equation set is solved, a solution of an initial quadratic nonlinear equation set is determined on the basis of the solved solution of the target linear equation set, a solution technology capable of meeting the quadratic nonlinear equation set is realized by utilizing the relevant characteristics of quantum, and the complexity and difficulty of solution are reduced. 本发明公开了一种基于量子线路的二次非线性方程组求解方法及装置，方法包括：获取目标线性方程组，目标线性方程组根据初始二次非线性方程组进行转化确定，构建量子线性求解器对应的量子线路，运行量子线路并测量，以对目标线性方程组进行求解，基于所求解出的目标线性方程组的解，确定初始二次非线性方程组的解，利用量子的相关